2015
DOI: 10.1111/avj.12360
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resolution of accidental intramuscular injection of Gudair® vaccine in a mare

Abstract: This case report describes the accidental intramuscular administration of 20 mL Gudair® vaccine to a 7-year-old Standardbred mare and successful treatment of the resulting inflammatory reaction by radical surgical resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
(38 reference statements)
1
3
0
Order By: Relevance
“…The mare was being treated by the owners with intramuscular procaine penicillin for a laceration, but a person unfamiliar with the treatment administered a large dose of Gudair® vaccine instead. Intramuscular administration of Gudair® caused severe, extensive myositis around the injection site similar to that described in sheep and humans …”
Section: Equinesupporting
confidence: 70%
“…The mare was being treated by the owners with intramuscular procaine penicillin for a laceration, but a person unfamiliar with the treatment administered a large dose of Gudair® vaccine instead. Intramuscular administration of Gudair® caused severe, extensive myositis around the injection site similar to that described in sheep and humans …”
Section: Equinesupporting
confidence: 70%
“…The development of lesions at the injection site following vaccination is recognised in sheep and cattle and is attributed to the oil-based adjuvant in the vaccine. 9 Accidental injection site lesions are also reported in humans 7,11 and in a horse, 8 with long-term morbidity in both species. The results of a study in a region of New South Wales with a high prevalence of OJD revealed a high proportion of lamb carcases carrying vaccination site lesions (64.2 AE 1.7%) compared with adult sheep (19 AE 2.6%).…”
Section: Discussionmentioning
confidence: 97%
“…3 The safety and efficacy of the vaccination has been investigated and although vaccination site reactions are reported, the benefit of vaccination is considered to outweigh the side effects. 7,8 The focus of concern over the incidence of these lesions is primarily the effect on carcase quality. This adjuvant is a Freund's complete adjuvant that is highly efficacious at stimulating a cell-mediated immune response and known to be reactive in human and animal tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation